PERBEDAAN TINGKAT KESEJAHTERAAN ANTAR KECAMATAN DI KABUPATEN KOTAWARINGIN BARAT - , B.Kusnandar ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Development is essentially not only to pursuit high growth rates, but also the equity which felt by the entire population. The fact that some new areas with higher welfare level compare to elder areas cannot be separated from the government's role as regulator in directing development. This study aimed to: (1) compare the level of welfare among population in districts of Kotawaringin Barat, (2) identify factors affecting such differences (3) measuring the government's role in affecting such differences. This study used deductive method with a qualitative descriptive approach. There are 6 sub-districts as the study sites and this study used secondary data which obtained from the relevant agencies and field survey result. The study found, Fist, the sub-district with higher category is Arut Selatan, intermediate category are Kumai and Pangkalan Lada, lower category are Pangkalan Banteng, Kotawaringin Lama and Arut Utara. Second, the main factor that causing the low levels of welfare is low accessibility and mobility, lack of basic infrastructure, and lack of budget financial support , the impact on low investments into the region, and vice vers. Third, the Government has a major contribution in creating a gap between these areas, it is evident by concentration of planning (allocation space) and implementation (budget allocation) to a specific region, which impacted on the gap toward existence of basic infrastructure. Fourth, the abundance of natural resources does not necessarily correlate positively with improved levels of welfare, as shown by condition of Kotawaringin Lama and Arut Utara with their extensive plantation land suitability and gold mines. Government stimulation is needed to improve accessibility, mobility and completeness of basic infrastructure to appeal investors. Fifth, the pattern of national gap is similar with province and regency levels.